Cervical pessary plus vaginal progesterone in a singleton pregnancy with a short cervix: an experience-based analysis of cervical pessary's efficacy. (12th December 2022) - França, Marcelo Santucci; Hatanaka, Alan Roberto; Cruz, Jader de Jesus; Andrade Júnior, Valter Lacerda de; Kawanami Hamamoto, Tatiana Emy; Sarmento, Stephanno G. P.; Elito Júnior, Júlio; Pares, David Baptista da Silva; Mattar, Rosiane; Araujo Júnior, Edward; Moron, Antonio Fernandes
Abstract: Background: Several studies were published about cervical pessary, with controversial results. These studies demonstrated that the patient follow-up after pessary insertion is very different between the study centers and the number of pessary insertions per center was often <30 cases. This study aims to determine cervical pessary performance in singleton pregnancies with a short cervix based on a single center learning curve. Methods: Between 2011 and 2018, 128 singleton pregnancies between 18 and 24 gestational weeks with a short cervix (<25 mm) were referred to our clinic. All cases were treated with progesterone, and when available in our supplies (due to low resources) cervical pessary was also offered. Three groups were created for statistical analysis: Group 1 ( n = 33), treated with progesterone-only; Groups 2 and 3, treated with cervical pessary plus progesterone. Group 2 included the first cases ( n = 30) of pessary, defined by a learning curve and cumulative sum analysis, while Group 3 included the subsequent 65 cases. The primary outcome was preterm birth (PTB) < 34 gestational weeks. Results: The learning curve was performed with all cases of pessary plus progesterone, and 30 patients were obtained as the number needed for learning, in our study with two operators. The PTB rate < 34 weeks was 27.3, 20, and 4.6% in groups 1, 2, and 3, respectively. There was no significant difference between Group 1 and 2 (OR 1.1; 95% CI 0.066 − 18.45; p = .945). When comparing Groups 1 and 3 there was a significant difference in PTB rates (OR 0.08; CI95% 0.01–0.42; p = .003). Considering Kaplan-Meyer Survival analysis, we can observe that the performance of progesterone alone (Group 1) was similar to Group 2 (progesterone + first 30 cases of pessary) ( p = .432), but the performance of Group 3 (progesterone + subsequent 65 cases of pessary) and Group 1 shows a statistically significant difference ( p = .011). Conclusion: Learning curve and cumulative sum analysis determined that the application and surveillance of at least 30 patients is required to see significant improvements in the primary outcome of PTB < 34 weeks.